A numerical model for estimation of water droplet size in the anode channel of a proton exchange membrane fuel cell. (December 2019) - Mohammadzadeh, Kazem; Kaldehi, Bahare Jahani; Jazmi, Ramin; Khaleghi, Hassan; Maddahian, Reza; Shirani, Ebrahim
Highlights: Water droplet size in the anode channel of a of proton exchange membrane fuel cell (PEMFC) is numerically estimated. Effects of working parameters of the PEMFC on the amount of produced water are investigated. A correlation for the produced water droplet size in the anode channel is proposed. Abstract: The effects of working conditions of the proton exchange membrane fuel cell (PEMFC) on the amount of produced water on the walls of the anode gas flow channel (GFC) were numerically investigated. For this purpose, a single-region, steady, two-dimensional, along-the-channel and non-isothermal model was used. Results showed quantitatively that by increasing the working temperature ( Tcell ), decreasing the relative humidity at the anode GFC inlet ( RHa ), increasing the current density ( i ) and increasing the hydrogen stoichiometry ratio ( SH2 ), the amount of produced water is reduced and consequently, water flooding is prevented. The numerical results also demonstrated that how the size of water droplet increases along the channel. In fact the increase in the size of the droplets with various working conditions were investigated and it was shown that RHa, Tcell and SH2 are the most effective in increasing the droplet size while the current density is the least responsible for this matter. Finally, a relationship for the size of the produced water droplets in the anode GFC as a function of the working parameters of a PEMFC was proposed which is applicable for the water management in the anode GFC.